APPLYING CLOZE EXERCISE PROCEDURES IN MASTERING READING COMPREHENSION - Sri Wahyuni (Visipena, 2014)
Cloze procedure is a technique in which words are deleted from a reading passage. In this study, researcher used purposive cloze that deleted content word, such as: noun, adjective and verb. The data taken from 43 students belong to both groups, the experimental group (22 students) and control group (21 students), of the second grade students of SMA Al-Falah Abu Lam-U. The instrument used for collecting the data is test in order to know the students’ achievement in completing nouns, adjectives and verbs, while pre-test and post-test in order to get the result of both groups. The result was analyzed by using statistical formula, such as by calculating the mean score, standard deviation and t-test in order to know whether there is the difference between experimental and control group performance in completing reading with content word deletion. The researcher used percentage formula in order to find out the difference of students’ achievement in completing noun, adjective, and verb deletions in reading passage and also to find out in what level the experimental and control group based on the cloze reading inventory level. Based on the data analysis, the writer found that there is a significant difference between cloze exercise for experimental group and conventional way for control group. It can be shown with the t-test result which is higher than the t-table result (9,41>2,02). It means that the researcher accepts her alternative hypothesis that there is a difference between both techniques, and cloze exercise technique is better than conventional technique. The deletion of verbs is quite easy for both groups. The average percentages of the post-test covers 66% noun, 59% adjective and 73% verb for the experimental group, while the control group results are 59% noun, 51% adjective and 61% verb. To support the data above, the researcher also divided the students’ achievement based on “cloze reading inventory level”. Most of the experimental students are in independent level with the average percentage 66% and few of them in instructional level. While in control group, only few of students are in independent level with the average percentage 58% and most of them are in instructional level.